Mechanics of snake biting: Experiments and modelling. (December 2020) - Kundanati, Lakshminath; Guarino, Roberto; Menegon, Michele; Pugno, Nicola M.
Abstract: Among all the vertebrates, snakes possess the most sophisticated venom delivering system using their fangs. Fangs of many animals are well adapted to the mechanical loads experienced during the functions such as breaking the diet and puncturing the skin of the prey. Thus, investigation and modelling of puncturing mechanics of snakes is of importance to understand the form-function relationship of the fangs and tissue-fang interactions in detail. We have thus chosen fangs of two snake species, i.e., viper ( Bitis arietans ) and burrowing snake ( Atractaspis aterrima ), with different shape and size, and performed insertion experiments using tissue phantoms. Our results showed that the fangs of both species have similar mechanical properties but there was a difference in the insertion forces owing to the difference in shape of the fang. Also, we developed an analytical model of the fang-tissue interaction and obtained a good agreement with the experimental results. Thus, our study can help in the development of bioinspired needles that can potentially have reduced insertion forces and optimised tissue penetration. Graphical abstract: Image 1